Desired Compensation Adaptive Robust Control of an Active Vibration Isolation System - Bo Zhao; Weijia Shi; Ming Zhang; Jiaxin Li; Feng Li (Complexity)
Active vibration isolation system (AVIS) has attracted increasing attention of researchers in precision engineering. In this paper, a desired compensation adaptive robust controller (DCARC) is proposed for an AVIS developed in our laboratory. The AVIS composed of one platform and three active isolators is required to achieve high-performance vibration isolation as well as low trajectory tracking error for positioning. The vertical three degrees of freedom (DOFs) and horizontal three DOFs are decoupled by the joint bearing of the isolators. The dynamic model of the system is built and is simplified to three single-input-single-output (SISO) systems. The DCARC control scheme is then proposed, which contains a deterministic robust control (DRC) term and an adaptive control (AC) term. The high performance in vibration isolation and positioning can be subsequently achieved, even the actual load and system stiffness are unknown and there exists direct bounded disturbance on the platform. The AC term is designed to estimate the unknown parameters of the system. The DRC term can improve the robustness of the system, which is used to reject the direct disturbance and the parameter estimation error. Furthermore, the computing time and the influence of the measurement noise can be reduced effectively by reason of desired compensation. The numerical simulation and comparative experiments are carried out under the conditions of using DCARC, DRC, and AC controllers. The experimental results validate that the proposed DCARC control strategy outperforms other control method and possesses both high-performance vibration isolation and low tracking error.